Compatibility of Atmospheric 14CO2 Measurements: Comparing the Heidelberg Low-Level Counting Facility to International Accelerator Mass Spectrometry (AMS) Laboratories. Issue 3 (19th September 2016) - Hammer, Samuel; Friedrich, Ronny; Kromer, Bernd; Cherkinsky, Alexander; Lehman, Scott J; Meijer, Harro A J; Nakamura, Toshio; Palonen, Vesa; Reimer, Ron W; Smith, Andrew M; Southon, John R; Szidat, Sönke; et al.
Abstract: Combining atmospheric Δ 14 CO2 data sets from different networks or laboratories requires secure knowledge on their compatibility. In the present study, we compare Δ 14 CO2 results from the Heidelberg low-level counting (LLC) laboratory to 12 international accelerator mass spectrometry (AMS) laboratories using distributed aliquots of five pure CO2 samples. The averaged result of the LLC laboratory has a measurement bias of –0.3±0.5‰ with respect to the consensus value of the AMS laboratories for the investigated atmospheric Δ 14 C range of 9.6 to 40.4‰. Thus, the LLC measurements on average are not significantly different from the AMS laboratories, and the most likely measurement bias is smaller than the World Meteorological Organization (WMO) interlaboratory compatibility goal for Δ 14 CO2 of 0.5‰. The number of intercomparison samples was, however, too small to determine whether the measurement biases of the individual AMS laboratories fulfilled the WMO goal.